Prevalência de osteoporose em mulheres acima de 50 anos, na pós-menopausa, atendidas no Hospital Universitário de Santa Maria entre 2016 e 2021 - Stamm, Daniel Neis (2023)
Menopause is the event that marks the end of a woman‟s reproductive capacity. It is defined after a period of 12 consecutive months of amenorrhea and is characterized by signs and symptoms resulting from ovarian function loss. This dysfunction leads to estrogen deficiency, which can cause various health problems, such as osteoporosis. Characterized by bone mass loss and deterioration of tissue microarchitecture, osteoporosis leads to decreased bone strength and an increased risk of fractures. Considered a chronic, multifactorial condition closely related to aging, it is estimated that the disease affects 200 million women worldwide, and that one in three women over 50 years old will experience an osteoporotic fracture. This study aimed to determine the prevalence of osteoporosis in postmenopausal patients treated at the University Hospital of Santa Maria (HUSM). To achieve this, an electronic medical record review was conducted to assess the prevalence of osteoporosis in postmenopausal women and to associate this outcome with clinical factors obtained through a data collection instrument proposed by the researchers. This cross-sectional study included 711 patients who underwent bone densitometry at the Radiology Service of HUSM between 2016 and 2021. Variables such as age, race, education, BMI, as well as clinical story including thyroid disorders, kidney and gastrointestinal tract diseases, smoking and alcohol consumption, rheumatoid arthritis, corticosteroid use, physical activity, previous osteoporotic fracture and family history of fractures were evaluated. The prevalence of osteoporosis found was 28.83% (n = 205). The mean age of women with osteoporosis was 66.6 years (SD±8.9). In this group, a higher proportion of women were white (95%) and had lower education levels (82.7% were illiterate or had only completed elementary school). Additionally, the lowest T-score values for the femur (-2.359; SD±0.953) and spine (-2.819; SD±1.023), femoral neck density (0,721; SD±0,114), and BMI (25.21; SD±4.82) were found in the osteoporosis group. This group also showed the highest percentages of corticosteroid use (41.7%) and previous fractures (15.2%), as well as lower levels of physical activity (15.2%). The data found were similar to those in the literature. The prevalence of osteoporosis was high, and the main factors associated with reduced bone mass were advanced age, white race, lower education level, lower BMI, lower femoral neck density, increased corticosteroid use, the presence of previous fractures, and lower physical activity. However, important variables for the development of the disease, such as smoking and alcohol comsuption, did not show a significant difference. It is important to note that this study has limitations as is is retrospective and does not involve direct interview with the patients. Therefore, the lack of data or incorrectly record-keeping may have influenced the overall results of the analysis. Despite this, investigating the risk factors is essential to improve the quality of care and, consequently, reduce the disease rate.